Associations between active trachoma and community intervention with Antibiotics, Facial cleanliness, and Environmental improvement (A,F,E). - Jeremiah Ngondi; Fiona Matthews; Mark Reacher; Samson Baba; Carol Brayne; Paul Emerson (PLoS Neglected Tropical Diseases)
Background Surgery, Antibiotics, Facial cleanliness and Environmental improvement (SAFE) are advocated by the World Health Organization (WHO) for trachoma control. However, few studies have evaluated the complete SAFE strategy, and of these, none have investigated the associations of Antibiotics, Facial cleanliness, and Environmental improvement (A,F,E) interventions and active trachoma. We aimed to investigate associations between active trachoma and A,F,E interventions in communities in Southern Sudan. Methods and findings Surveys were undertaken in four districts after 3 years of implementation of the SAFE strategy. Children aged 1-9 years were examined for trachoma and uptake of SAFE assessed through interviews and observations. Using ordinal logistic regression, associations between signs of active trachoma and A,F,E interventions were explored. Trachomatous inflammation-intense (TI) was considered more severe than trachomatous inflammation-follicular (TF). A total of 1,712 children from 25 clusters (villages) were included in the analysis. Overall uptake of A,F,E interventions was: 53.0% of the eligible children had received at least one treatment with azithromycin; 62.4% children had a clean face on examination; 72.5% households reported washing faces of children two or more times a day; 73.1% households had received health education; 44.4% of households had water accessible within 30 minutes; and 6.3% households had pit latrines. Adjusting for age, sex, and district baseline prevalence of active trachoma, factors independently associated with reduced odds of a more severe active trachoma sign were: receiving three treatments with azithromycin (odds ratio [OR] = 0.1; 95% confidence interval [CI] 0.0-0.4); clean face (OR = 0.3; 95% CI 0.2-0.4); washing faces of children three or more times daily (OR = 0.4; 95% CI 0.3-0.7); and presence and use of a pit latrine in the household (OR = 0.4; 95% CI 0.2-0.9). Conclusion Analysis of associations between the A,F,E components of the SAFE strategy and active trachoma showed independent protective effects against active trachoma of mass systemic azithromycin treatment, facial cleanliness, face washing, and use of pit latrines in the household. This strongly argues for continued use of all the components of the SAFE strategy together.